2021
DOI: 10.1007/s10853-021-06056-0
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale phase separations in as-fabricated thick super duplex stainless steels

Abstract: Nanoscale phase separations, and effects of these, were studied for thick super duplex stainless steel products by atom probe tomography and mechanical testing. Although nanoscale phase separations typically occur during long-time service at intermediate temperatures (300–500° C, our results show that slowly cooled products start to develop Fe and Cr separation and/or precipitation of Cu-rich particles already during fabrication. Copper significantly slowed down the kinetics at the expense of Cu-rich particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This understanding becomes particularly important for thick gauge sections of SDSS where it is not possible to cool the whole gauge thickness equally after solution treatment. In a recent study [17], it was shown that PS already occurs in the ferrite of asfabricated thick hot-rolled SDSS. This, therefore, raises the concern how the gauge thickness influences the PS during heat treatment and subsequent aging during service.…”
Section: Introductionmentioning
confidence: 96%
“…This understanding becomes particularly important for thick gauge sections of SDSS where it is not possible to cool the whole gauge thickness equally after solution treatment. In a recent study [17], it was shown that PS already occurs in the ferrite of asfabricated thick hot-rolled SDSS. This, therefore, raises the concern how the gauge thickness influences the PS during heat treatment and subsequent aging during service.…”
Section: Introductionmentioning
confidence: 96%
“…However, some studies have shown that in highly alloyed DSS such as super duplex stainless steels (SDSS), nanostructure changes can be present already in as-received materials. [9,10] In samples with low Cu content, the main phenomenon was Fe and Cr phase separation, while in Cu-containing SDSS, CRPs were also present in the ferrite. Therefore, 475 °C-embrittlement in SDSS may happen during short aging times such as overheating, fire, long cooling after fabrication, etc.…”
Section: Introductionmentioning
confidence: 99%
“…As the heat input during welding increases, it leads to abnormal grain growth within the weld. Additionally, a substantial amount of ferrite is generated, diminishing the microstructure and properties of the weld [4,[12][13][14][15]. Hence, activated-flux TIG welding (A-TIG) has emerged as a primary welding process for thick-walled structural parts made of 1Cr21Ni5Ti duplex stainless steel.…”
Section: Introductionmentioning
confidence: 99%